ANTIOXIDATIVE ACTIVITY AND PHYTOCHEMISTRY PROFILE OF HIBISCUS SABDARIFFA HERB EXTRACTS - FITROTUNNISA, QOTRUNNADA; ARSIANTI, ADE; TEJAPUTRI, NADZILA ANINDYA; QORINA, FONA (International Journal of Applied Pharmaceutics, 2019)
Objective: Hibiscus sabdariffa, known as Roselle, is a widely-cultivated herb in Indonesia and has been consumed as an herbal drink due to its medicinal properties. The purpose of this research is to identify the antioxidant activity and phytochemical profile of Hibiscus sabdariffa. Methods: The Hibiscus sabdariffa samples were extracted and macerated with three different organic solvents: ethyl acetate, ethanol, and n-hexane. These extracts were then analyzed using thin layer chromatography (TLC) and phytochemical tests to identify the extracts’ secondary metabolites. The extracts’ antioxidant activity was evaluated using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) method. Results: The phytochemistry tests were positive for glycosides, alkaloids, steroids, triterpenoids, tannins, and flavonoids. The TLC analysis revealed that the extracts containing two to three organic compounds. The ethanol Hibiscus sabdariffa extracts with an IC50 value 103.63 ppm showed stronger antioxidant activity than the ethyl acetate extract. Conclusion: Ethanol Hibiscus sabdariffa extracts may be a potential source of natural antioxidant.